Strategi Pengembangan Mutu Ikan Asin Jambal Roti (Ikan Manyung) di Karangsong Kabupaten Indramayu: Strategy for Quality Development of Salted Jambal Roti (Aarid catfish) in Karangsong, Indramayu - Talim Sumarno; Tri Winarni Agustini; Azis Nur Bambang (Jurnal Pengolahan Hasil Perikanan Indonesia, 2020)
Jambal roti salted fish processing in Karangsong, Indramayu District is still a traditional business. Thus their handling and processing need to implement a quality management system for standardizing the quality of the products. This study was aimed to analyze a strategy fo developing high quality of salted jambal roti in Karangsong, Indramayu District. The analysis used a combination of SWOT and QSPM. Key respondents were fishery supervisors, provincial/regional quality mentors, SME supervisors, academics and consumers. Five alternative development strategies were proposed to develop high quality of jambal roti. These five strategies are (1) improving product quality and service quality to consumers; (2) strengthening and developing integrated fish processing groups; (3) socializing and training related to Indonesian National Standard (INS); (4) facilitating the administration of the MSME fish processing industry; and (5) looking for business partners for business development.